Clinical evaluation of complete denture fabricated using two different final impression techniques on masticatory efficiency and oral health-related quality of life - Uttkarsh Shah; Neerja Mahajan; Ninad Bhatt (Wolters Kluwer Medknow Publications, 2022)
Aim: To compare the effect of complete denture fabricated using selective pressure impression and functional impression technique on masticatory efficiency and oral health-related quality of life (OHRQoL) in patients with resorbed ridges. Settings and Design: A randomized two arm, parallel group study. Materials and Methods: Forty-eight participants with set inclusion and exclusion criteria were randomly allocated into two groups. Complete denture was fabricated in Group A and Group B using selective pressure and functional impression technique, respectively. The follow-up was done at 3 months. Masticatory efficiency was measured by color-changing chewing gum, and OHRQoL was assessed using the Geriatric Oral Health Assessment Index (GOHAI) Hindi Version. Statistical Analysis Used: The Wilcoxon signed-rank test was applied to check the intergroup analysis for the GOHAI scores of both impression techniques. The Mann-Whitney U test was applied to compare intragroup analysis for masticatory efficiency and the GOHAI scores of both the techniques. Results: A total of 45 participants completed the follow-up. The mean age of the total participants was 62.7 ± 3.8. No statistically significant difference (P > 0.05) was observed between the masticatory efficiency and post-GOHAI scores of both the impression techniques. Conclusion: Selective pressure and functional impression techniques may be successfully used to fabricate complete dentures for patients with resorbed ridges.